Forests and floods: Using field evidence to reconcile analysis methods. Issue 15 (5th June 2020) - Bathurst, James C.; Fahey, Barry; Iroumé, Andrés; Jones, Julia
Abstract: The extent to which forests, relative to shorter vegetation, mitigate flood peak discharges remains controversial and relatively poorly researched, with only a few significant field studies. Considering the effect purely of change of vegetation cover, peak flow magnitude comparisons for paired catchments have suggested that forests do not mitigate large floods, whereas flood frequency comparisons have shown that forests mitigate frequencies over all magnitudes of flood. This study investigates the apparent inconsistency using field‐based evidence from four contrasting field programmes at scales of 0.34–3.1 km 2 . Repeated patterns are identified that provide strong evidence of real effects with physical explanations. Magnitude and frequency comparisons are both relevant to the impact of forests on peak discharges but address different questions. Both can show a convergence of response between forested and grassland/logged states at the highest recorded flows but the associated return periods may be quite variable and are subject to estimation uncertainty. For low to moderate events, the forested catchments have a lower peak magnitude for a given frequency than the grassland/logged catchments. Depending on antecedent soil saturation, a given storm may nevertheless generate peak discharges of the same magnitude for both catchment states but these peaks will have different return periods. The effect purely of change in vegetation cover may be modified by additional forestry interventions, such as road networks and drainage ditches which, by effectively increasing the drainage density, may increase peak flows for all event magnitudes. For all the sites, forest cover substantially reduces annual runoff. Abstract : Conceptual model of forest impact on floods. Comparison of peak discharges for forested and unforested catchments as a function of (a) rainfall event return period and (b) flood return period.